Peran Program Kelas Literasi dalam Meningkatkan Kemampuan Literasi Informasi Mahasiswa Universitas Nahdlatul Ulama Yogyakarta - Almer Samantha Hidaya; Marwiyah Marwiyah (Pustabiblia: Journal of Library and Information Science, 2020)
The rapid development of information technology makes information spread and open which can be accessed from anywhere and at any time. The development of information technology must also be balanced with the ability to search and identify information properly and correctly, which is then known as information literacy. But this ability is not yet fully owned by information users, especially students. This makes the ability of information literacy is an urgent matter, especially on scientific information. Departing from the low level of scientific information literacy, students need to receive scientific information literacy training, especially in the early years of lectures. This research uses research and development (RD) methods. Literacy class participants used as informants in this study were determined randomly, which came from the first year students of each study program in the academic year 2019/2020. In the initial stage of this study a measurement of the level of knowledge and literacy ability of students of trainees (classes) was carried out using a pretest. In the next stage class material was carried out as well as practice in order to obtain results in the form of applied skills that could be directly applicable. The material includes general knowledge about scientific information, effective search methods and strategies, searching of electronic journal portal both paid and open access, as well as using and evaluating information including citations. At the final stage of this study a posttest was conducted to see the extent of the effectiveness of this training model and class participants’ understanding of scientific information literacy after attending literacy classes. The results of this program show an increase in students’ information literacy skills.